On the Feasibility of Unlicensed Communications in the TV White Space: Field Measurements in the UHF Band. (23rd February 2015) - Fadda, M.; Popescu, V.; Murroni, M.; Angueira, P.; Morgade, J.
Abstract : In practical unlicensed communications in TV band, radio devices have to identify, at first, the transmission opportunities, that is, the portion of the spectrum licensed for broadcasting services unoccupied in a certain region at certain time, that is, the so-called TV white space. In this paper the outcome of field measurements in the UHF TV band (470–860 MHz) conducted in EU is presented. To obtain empirical values for the parameters upon which unlicensed radio devices are able to distinguish in a real scenario between empty and occupied TV channels, signal power measurements have been performed in Italy, Spain, and Romania on rural, suburban, and urban sites, at different heights over the ground by using different analysis bandwidths. The aim of this work is to provide a set of practical parameters upon which harmless unlicensed communication in the UHF TV white space is feasible. The results have been analyzed with respect to the hidden node margin problem, spectrum sensing bandwidth, and occupancy threshold.